2019
DOI: 10.1111/ejss.12810
|View full text |Cite
|
Sign up to set email alerts
|

Comparing chemical extraction and a piecewise function with diffusive gradients in thin films for accurate estimation of soil zinc bioavailability to Sedum plumbizincicola

Abstract: Summary Accurate evaluation of metal bioavailability to hyperaccumulators is necessary for prediction of metal uptake and estimation of phytoextraction potential. Sedum plumbizincicola X.H. Guo et S.B. Zhou ex L.H. Wu (Crassulaceae), a hyperaccumulator of cadmium (Cd) and zinc (Zn), was grown in a pot experiment in 108 agricultural soils representing a wide range of typical Chinese soil types. The contribution of soil properties to Zn uptake was assessed quantitatively. Soil total Zn, soluble Zn, CaCl2‐extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…A new type of resin gel combined with layered double hydroxide nanoparticles changed with diethylenetriaminepentaacetic acid was created for the use of DGT tools to measure eight anions and cations in waters and soils (Wang et al 2023b ). A hyperaccumulator plant of Cd and Zn, Sedum plumbizincicola , was grown in a pot experiment (Zhou et al 2019 ). Soil total Zn and water soluble, CaCl 2 -extractable, and C DGT Zn concentrations were measured and used to predict the shoot Zn concentration.…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
“…A new type of resin gel combined with layered double hydroxide nanoparticles changed with diethylenetriaminepentaacetic acid was created for the use of DGT tools to measure eight anions and cations in waters and soils (Wang et al 2023b ). A hyperaccumulator plant of Cd and Zn, Sedum plumbizincicola , was grown in a pot experiment (Zhou et al 2019 ). Soil total Zn and water soluble, CaCl 2 -extractable, and C DGT Zn concentrations were measured and used to predict the shoot Zn concentration.…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
“…Using liquid chromatography coupled to high-resolution mass spectrometry (LC-QTOF-MS), Brock et al (2020) developed a novel method for non-target screening of leaf litter-derived dissolved organic matter. CaCl 2 extraction was shown to be more appropriate than diffusive gradients in thin films (DGT) for estimating zinc (Zn) bioavailability to Sedum plumbizincicola when comparing chemical extraction and DGT techniques (Zhou et al, 2019). Laser-induced breakdown spectroscopy (LIBS) and partial least squares regression (PLSR) were used for rapid, on-site quantitative analysis of potentially toxic metals in wet soil samples, and the results showed that LIBS technology can detect these metals with high sensitivity and specificity (Xu et al, 2022).…”
Section: Soil Chemistrymentioning
confidence: 99%